The effectiveness of integrating Ed-venture learning platform into the operations department of British American Tobacco Bangladesh (BATB) - Ahmed, Tamanna (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.